Taktik Efektif Guru Guna Membangun Motivasi Belajar Siswa Kelas V Di SD Negeri Tempel Krian Sidoarjo - Eva Khusnia Arianti; Rizky Herdian Syah; Mila Hariani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to identify and analyze effective tactics used by teachers in increasing the learning motivation of fifth grade students at Tempel Elementary School. Using a qualitative approach with a case study method, data was collected through classroom observations, in-depth interviews, and document analysis. The research results show that several effective tactics include: (1) Project-Based Learning Approach which involves students in practical and relevant activities, (2) Use of varied learning media such as educational videos and teaching aids to make lessons more interesting, (3) Providing Constructive Feedback that helps students feel valued and motivated, (4) Creation of a Positive and Supportive Classroom Environment that makes students feel safe to participate, and (5) Use of Interactive Learning Methods such as group discussions and educational games that increase students' active participation. These findings indicate that these strategies effectively increase students' learning motivation, which contributes to increasing their participation, interest and learning outcomes. This research provides practical implications for teachers in developing effective teaching strategies and becomes a reference for developing teacher training programs and educational policies that support the creation of a learning environment that motivates students.